Patentability potential of natural products for xerostomia treatment - Burci, Lígia Moura; Barbosa, Paula Bianca Dias; da Silva, Cristiane Bezerra; Zanin, Sandra Maria Warumby; Miguel, Obdulio Gomes; Dias, Josiane de Fátima Gaspari; Miguel, Marilis Dallarmi (Brazilian Dental Science, 2016)
Xerostomia is characterized as a symptom caused by hyposalivation, which can occur for reasons such as age, polypharmacy, radiation therapy, among others. Currently,few products are available for the treatment of xerostomia, which is a subject still underestimated by many health professionals. Thus, we searched patents applied and approved in Brazil on xerostomia, to verify the existing innovation involving natural products. We found 33 patents applied and approved in Brazil, many of them using acids derived from natural products such as sialologue agents. This significant number of patents demonstrates the relevance of the themeand the need for more studies involving the potential use of natural products to relieve symptoms. Keywords Xerostomia; Natural products and patents.